Comprehensive genomic analysis of hypocholesterolemic probiotic Enterococcus faecium LR13 reveals unique proteins involved in cholesterol-assimilation - Aswal, Manisha; Singhal, Neelja; Kumar, Manish (Frontiers in Nutrition, 2023)
Hypercholesterolemia is a major risk factor for cardiovascular diseases (CVDs). Chemotherapeutic agents for CVDs exhibit several side effects. Specific probiotics with hypocholesterolemic effects can be safe and effective alternatives to chemotherapeutics. Here, we have analysed and compared the genome of a novel rhizospheric Enterococcus faecium LR13 cholesterol-assimilating probiotic with other probiotic/pathogenic E. faecium strains to discern genetic factors underlying probiotic efficacy and cholesterol-assimilation. Pan-genomic analyses of probiotic/pathogenic strains revealed that LR13 and WEFA23 (cholesterol-assimilating probiotics) harboured 21 unique proteins absent in non-cholesterol-assimilating probiotics. Of these, 14 proteins could directly help in cholesterol-assimilation by producing short chain fatty acids, lipid (sterol) transport and membrane stabilization, and bile salt hydrolase activity. This suggests that cholesterol-assimilation is an intrinsic, strain-specific trait exhibited by probiotics with a specific genetic constitution. Moreover, the unique proteins identified in this study can serve as biomarkers for discerning/characterizing cholesterol-assimilating probiotics as novel biotherapeutics against CVDs.